A Comparative Study on Uplink Sum Capacity with Co-Located and Distributed Antennas - Dai, Lin (IEEE journal on selected areas in communications, 2011)
It has been long believed that the distributed antenna system (DAS) has great potentials for capacity improvement compared to the traditional cellular system with co-located base-station antennas. Intuitively, the distributed characteristic of antennas provides a much more efficient utilization of spatial resources. It, however, also significantly complicates the channel modeling and system analysis. Despite an increasing amount of academic attention and industrial interest, how to characterize the capacity advantages of the DAS in the multiuser scenario remains largely unknown. In this paper, we present a comparative study on the uplink ergodic sum capacity with multiple base-station antennas either co-located or uniformly distributed within a given area. We demonstrate that under the same consumption of transmission power, enormous gains can be achieved by the distributed antenna layout thanks to (1) reduced minimum access distance of each user; and (2) enhanced channel fluctuations which provide a significant boost to the sum capacity when the channel state information is available at both the transmitter and the receiver sides. We further apply the analysis to a cellular system with full cooperation among base stations. The comparison verifies that the DAS yields a much higher sum capacity, and capacity gains increase with the number of base-station antennas per cell.